The Greeks crucible of civilization - Harrison, Cassian; Neeson, Liam; Public Broadcasting Service (U.S.) ([Alexandria, VA] PBS DVD Gold, 2000)
Recounts the rise, glory, demise and legacy of the Greek empire, the astonishing civilization which marked the dawn of Western culture
Director of photography, Lee Pulbrook; editors, Mel Quigley, Maggie Coyee, Scott McEwing; music, Simon Fisher Turner, Michael Gibbs
Narrator, Liam Neeson
DVD stereo
Closed-captioned
1
Keywords: Civilization, Classical; Documentary television programs; Historical television programs; Greece -- Civilization -- To 146 B.C; Greece -- History -- To 146 B.C